2022
DOI: 10.3389/fenvs.2022.901924
|View full text |Cite
|
Sign up to set email alerts
|

Macrophyte habitat architecture and benthic-pelagic coupling: Photic habitat demand to build up large P storage capacity and bio-surface by underwater vegetation

Abstract: Macrophytes play an important role in shallow lakes if large standing crop can be achieved. Here we stress the role of submerged macrophytes for benthic-pelagic coupling in the shallow oxbow lake Alte Donau (Austria) during restoration triggered by sufficient light availability (12% surface ambient light, photic>12% depth, zoptimum) in both, the benthic and the pelagic habitat. Focusing on zoptimum, rather than on minimum light requirement (euphotic depth), seemed to be more meaningful to follow the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 115 publications
1
0
0
Order By: Relevance
“…The allelochemicals of T. dealbata should also be present in polycultures (despite of lower 4), but also seemed to contribute disproportionately to the biomass increase in polycultures (Figure 2). This echoes studies that found plants with extensive growth of roots and leaves speeded up nutrition absorption more than medium or small-sized plants (Liu et al, 2020;Teubner et al, 2022), which points out that it is essential to have species of large sizes considered and selected in CWs and sewage treatment (Levi et al, 2015). During our experiment, only the individuals of C. indica and T. dealbata entered the flowering stage, and reproduction might have elevated the uptake of various nutrients as well.…”
Section: Discussionsupporting
confidence: 77%
“…The allelochemicals of T. dealbata should also be present in polycultures (despite of lower 4), but also seemed to contribute disproportionately to the biomass increase in polycultures (Figure 2). This echoes studies that found plants with extensive growth of roots and leaves speeded up nutrition absorption more than medium or small-sized plants (Liu et al, 2020;Teubner et al, 2022), which points out that it is essential to have species of large sizes considered and selected in CWs and sewage treatment (Levi et al, 2015). During our experiment, only the individuals of C. indica and T. dealbata entered the flowering stage, and reproduction might have elevated the uptake of various nutrients as well.…”
Section: Discussionsupporting
confidence: 77%